Insoluble soybean polysaccharides: Obtaining and evaluation of their O/W emulsifying properties - Porfiri, María Cecilia (2017)
The aims of this work were to obtain different samples of insoluble soybean polysaccharides (ISPS) from defatted soy flour and to study their potential application as O/W emulsifier. In this regard, the insoluble residue (okara) resulting from an aqueous extraction (60 °C, pH 9.0), was submitted to an acidic extraction (pH 3.5, 120 °C) without or with a pretreatment (high pressure homogenization or sonication treatment). The insoluble residues of these extractions were dried (oven, 70 °C or vacuum post-treatment with 2-propanol, 40 °C) yielding different ISPS samples. Aqueous dispersions of ISPS samples (1?2% w/w, pH 3 and 7), were used to prepare coarse and fine O/W emulsions. Emulsion stability against creaming and coalescence processes, and the rheological behavior were analyzed. ISPS samples obtained by okara pretreatment and vacuum dried post-treatment with 2-propanol allow to produces emulsions with high values of flocculation degree, increasing the stability of the particle size, and allowing the formation of stronger gel-like emulsions. These pretreatments expose internal sites of the polysaccharide and protein structures, increasing their superficial hydrophobicity and, therefore, allow a strong absorption of the macromolecules at the oil-water interface and/or the formation of external layers, increasing the rigidity of the interfacial film and contributing to the formation of hydrated flocs, Also, these treatments could solubilize certain compounds in okara that would interfere negatively in the formation of the interfacial film. Particularly, sample obtained by high pressures homogenization of the okara presented the best emulsifying properties and it was not significantly affected by variations in the pH of the emulsion. The results of this research work demonstrate a high potential of application of the ISPS samples as O/W emulsifier, under acid and neutral conditions, increasing the added value of an important by-product of the soybean industry.